تحرير التجارة الدولية كأحد الأساليب الترغيبية لجماعات الضغط الاقتصادية الدولية - زنبوعة زياد; أبا زيد ثناء; ناصر سمير (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إن جماعات الضغط الاقتصادية الدولية عبارة عن تكتلات اقتصادية دولية أو منظمات أو مؤسسات اقتصادية متعددة الجنسية تنشئها وتسيطر عليها الدول الرأسمالية المتقدمة وذلك لتحقيق طموحاتها في فرض النموذج الغربي " النيوكلاسيكية " في اقتصاد السوق على الساحة الدولية. ومن أهم هذه الجماعات منظمة التجارة الدولية والشركات المتعددة الجنسية والاتحاد الأوروبي وصندوق النقد والبنك الدوليين. وقد تناولت مفهوم جماعات الضغط الاقتصادية الدولية وتحرير التجارة الدولية كأحد أساليبها الترغيبية. حيث أن جماعات الضغط الاقتصادية الدولية تجبر البلدان النامية على تحرير التجارة بشكل كلي وبالتالي التوجه مباشرةً نحو اقتصاد السوق وإضعاف دور القطاع العام والتخلي عن دور الدولة الاقتصادي والسياسي. كل هذا من أجل تحقيق الهيمنة على البلدان النامية والاقتصاد العالمي والتحكم به وامتلاك مصادر ثرواته. International pressure groups are multinational economic blocs and organizations are founded and controlled by advanced capitalist states in order to realize their aims of imposing Western "New liberalism" worldwide. Among the most important of such groups are The World Trade Organization, the multinational companies, The European Union, The International Monetary Fund, and The World Bank. This study deals with the concept of pressure groups and world trade liberalization as promoting styles. These blocs impose complete trade liberalization on developing countries, forcing them to adopt market economy. Thus, the public sector in the developing countries is weakened, and governments are forced to relinquish their economic and political role. The aim of all such policies by the pressure blocs is to control developing countries, dominate the world market, and control world resources.